2012
DOI: 10.1209/0295-5075/97/20004
|View full text |Cite
|
Sign up to set email alerts
|

Fish play Minority Game as humans do

Abstract: Previous computer simulations of the Minority Game (MG)1 have shown that the average agent number in the winning group (i.e., the minority group) had a maximal value such that the global gain was also maximal when an optimal amount of information was available to all agents 2 . This property was further examined 8 3and its connection to financial markets has also been discussed 9 .Here

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…(iii) Extending controlled experiments from human beings to other animals like ants [158] or fish [159] could be of value to study statistical physics of other kinds of adaptive agents beyond human beings. By doing so, people could understand those animals more by using concepts or tools originating from the traditional statistical physics.…”
Section: Three Directions For Future Researchmentioning
confidence: 99%
“…(iii) Extending controlled experiments from human beings to other animals like ants [158] or fish [159] could be of value to study statistical physics of other kinds of adaptive agents beyond human beings. By doing so, people could understand those animals more by using concepts or tools originating from the traditional statistical physics.…”
Section: Three Directions For Future Researchmentioning
confidence: 99%
“…Chmura et al (2010) conclude that the observed heterogeneity in players' behavior in games where multiple equivalent equilibria are present must be ascribed to the structure of individuals' preferences rather than to their inability to calculate mixed equilibria. Finally, Liu et al (2010) study minority game properties by comparing behavior in the game played by humans and by sh, and discover several behavioral similarities between the two species.…”
Section: Literature Reviewmentioning
confidence: 99%